Once They Were Eagles : The Men of the Black Sheep Squadron - Walton, Frank E., 1909- (Book collections on Project MUSE., 1986)
Describes the aerial battles, victories, and losses of "Pappy" Boyington's Black Sheep Squadron in World War II. Includes interview with Skaneateles, New York resident, Robert McClurg (p.135-137) who was a member of the Black Sheep Squadron